Soil humidity and evapotranspiration under three coffee (Coffea arabica L.) planting densities at Naranjal experimental station (Chinchiná, Caldas, Colombia) - Leidy Natalia Bermúdez- Flórez; José Régulo Cartagena-Valenzuela; Víctor Hugo Ramírez- Builes (Acta Agronómica)
Coffee cultivation depends on water supplied by rain or irrigation, which, in turn, affect productivity and harvest distribution. Knowing the influence of plant spacing on the behavior of soil moisture and water consumption, is likely to determine a crop’s planting density, fertilization and planting times, all based on regional water availability. In this context, the study was conducted at Naranjal Experimental Station, municipality of Chinchiná (Caldas, Colombia) at 04° 58’ N, 75° 39’ W; 1,381 m a.s.l., aimed to describe moisture performance in a coffee plantation established on  an Andisol, under three planting densities. This was done by estimating the evapotranspiration (ETo) and assessing crop evapotranspiration (ETc). Soil moisture was measured with a capacitance probe equipped with sensors spaced at 10, 20, 30, 40, 60 and 100 cm. Moisture content in the soil profile varied with planting density and from dry to humid periods. ETo and ETc were observed to be influenced by weather conditions, which determined higher values during the dry season and lower ones in the rainy season. Although planting density was found to affect hydraulic soil properties, sufficient water supply for the plants along both humid and dry seasons was stabilized by the water storage capacity that characterizes Andisols. The capacitance probe constitutes an effective tool for studying water performance in soils with coffee vocation in Colombia, especially when they are sensitive to the limitations imposed by water deficit resulting, in turn, from current or future climate variability.